Personal Awareness, Group Norms, Social Support and Active Participation in Sport for Madrasah Tsanawiyah Students - Syakur, Muhammad; Aswara, Agung Yuda; Bekti, Susilo; Sunuyeko, Nurcholis (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
Regular physical activity has a positive effect on human health, one of which can make our bodies fit. This study aims to determine the relationship between personal awareness, group norms, social support and active participation in sports for Madrasah Tsanawiyah students. This secondary research discusses and processes data provided by the Center for the Study of Physical Literacy and Sports Education at the IKIP Budi Utomo Malang Graduate School. The population of this study is unlimited because obtained by snowball sampling technique. While the sample is 343 Madrasah Tsanawiyah students in 2021. Data analysis techniques use correlation tests and path analysis tests. The results of this study indicate that: 1) there is a relationship between personal awareness and the norms of group sports, 2) there is a relationship between personal awareness and social support for sports both directly and indirectly through the norms of the Madrasah Tsanawiyah student groups, 3) there is a relationship between awareness personal and active participation in sports both directly and indirectly through group norms and social support. The conclusion of this study is that personal awareness, group sports norms, and social support contribute positively to the active sports participation of Madrasah Tsanawiyah students.